2003
DOI: 10.1063/1.1567050
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of porosity and dielectric constant of fluorocarbon porous films synthesized by using plasma-enhanced chemical vapor deposition and solvent process

Abstract: Fluorocarbon films obtained in plasma-enhanced chemical vapor deposition with a C 4 F 8 compound were composed of a carbon cross-linked network and unlinked species encapsulated in the network ͓J. Appl. Phys. 89, 893 ͑2001͔͒. The unlinked species were effectively removed from the films. Then, the network probably containing the pore of the species was extracted on wafers when the films were dipped into tetrahydrofran ͑THF͒ solvent. The fact implied that fluorocarbon porous films with a low-dielectric constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
(7 reference statements)
1
12
0
Order By: Relevance
“…They concluded that in such films ''an interconnected network of voids is present.'' Their observations are consistent with those of Takahashi et al 55 and Takahashi and Tachibana 56 who found that a-C:F films grown by PECVD from a C 4 F 8 monomer consist of a carbon cross-linked network and unlinked species encapsulated in the network. By using a dissolving technique that does not alter the film structure, they managed to obtain porous films with a pore size estimated to be a few subnanometers.…”
Section: Dielectric Strengthsupporting
confidence: 92%
“…They concluded that in such films ''an interconnected network of voids is present.'' Their observations are consistent with those of Takahashi et al 55 and Takahashi and Tachibana 56 who found that a-C:F films grown by PECVD from a C 4 F 8 monomer consist of a carbon cross-linked network and unlinked species encapsulated in the network. By using a dissolving technique that does not alter the film structure, they managed to obtain porous films with a pore size estimated to be a few subnanometers.…”
Section: Dielectric Strengthsupporting
confidence: 92%
“…Fluorocarbon (FC) films have been widely studied because of their remarkable properties, including a low dielectric constant (1.6-2.1) [1], biocompatibility [2,3], and superhydrophobicity [4,5]. Applications for such films include dielectric layers for the ultra-large scale integration devices, biopassivation coatings for implantable devices, and hydrophobic layers on paper.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Technology Roadmap for Semiconductors (ITRS) [1], however, ILDs with even lower dielectric constants are called for, and many studies [2,3,11,[14][15][16][17] have made efforts to further reduce the dielectric constants mainly by adjusting the porosity of films. In addition, some recent studies [18][19][20][21] proposed methods for utilizing air as ILDs.…”
Section: Introductionmentioning
confidence: 99%